Endophytic fungi colonize agricultural and non agricultural plants in Bedugul, Bali and their antifungal activity against Rhizoctonia solani Kuhn - Suciatmih Suciatmih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
Isolation of endophytic fungi was done to find alternative microorganisms as antifungal agent against Rhizoctonia solani Kuhn, a soil borne pathogen on many agricultural plants. The research objectives were 1) to isolate and identify endophytic fungi colonize agricultural and non-agricultural plants growing in Bedugul, Bali; and 2) to detect for their antifungal activity against R. solani under in-vitro conditions. The results indicated that 114 isolates of endophytic fungi were isolated from flowers, fruits, leaves, petioles, and stems of agricultural and non-agricultural plants. Ten isolates (8.8 %) were identified to species, 91 isolates (79.8 %) to genus, and 13 isolates (11,4 %) did not have spores that could not be identified morphological characters and classified as unidentified isolates. Endophytic fungi isolated including in group of Aspergillus, Bipolaris, Cladosporium, Colletotrichum, Corynesporopsis, Curvularia, Diplodia, Fusarium, Guignardia, Nigrospora, Pestalotiopsis, Phomopsis and Xylaria. Of the 114 fungal isolates tested, only 13 isolates (11.4 %) inhibited the growth of R. solani from 10.3 % to 62.2 % with a percent inhibition. The highest growth inhibition of R. solani was shown by Aspergillus niger isolated from Solanum licopersicum L. var cerasiforme (62.2 %). It could be concluded that the agricultural and non-agricultural plants growing in Bedugul, Bali were colonized by endophytic fungi. Aspergillus niger will be further examined on a field scale.